(3GdSHY GdeKGfjs - (3GdgQhj GdCUagGfj GdMGFQj, eMeO Jbj, eMeO GdgQhj, eMeO Jbj Hf MSjf Hf Ydj, J (B1299(3g` (B1882(3es
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg hSdGe Ydi YHGOg GdPjf GUWai (B... (3aChd GdHGH GdNGeS ajeG jJYdb HCMhGd CQHYI ef GdCeI GdeYUhejf Ydj Hf GdMSjf heMeO Hf Ydj HGbQ Ydhe GdChdjf hGdBNQjf hLYaQ Hf eMeO GdUGObs
(3BNQgG (B:s
(3BNQgG(B: (3Ke CMeQ MJi UGQ cGdYdb GdeMeQ Ke GNVQ MJi UGQ cCNVQ eG jchf ef GdCZUGf GdhQbI GdNVQI Ke JfGbV LSeg MJi UGQ aj UhQJgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L(B3: 179s
(3GdPQjYI, L (B12: 94s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs